Älgens och skogshönsens nyttjande av ett två år gammalt brandfält - Kårehagen, Alice; Jakob, Hannah Sophie (2022)
Forest fires have had an extensive impact on our landscapes. Natural forest fires are especially important for the regeneration of pine and nutrition cycle in the boreal zone. Fire suppression has become more and more effective over the last centuries, as modern forestry practices are based on different regeneration methods and fires are perceived as a danger to the public and the economical values of the forest. Due to climate change, which is believed to bring warmer and drier summers, forest fires may become more frequent and more extensive. Moose, Alces alces, and grouse, Tetraoninae, are characteristic species in the Swedish forests. Both species are interesting for hunters and generate nature encounters for both native and foreign tourists. However, the moose population causes substantial browsing damage in the Swedish forests and is involved in traffic accidents. This study aims to examine how burned forest patches are used by moose and grouse in comparison to unburned forest areas in Ljusdal, Sweden, after the major fire outbreaks in 2018. We also aimed to determine if there is a difference in browsing pressure by moose and frequency of damages in burned versus unburned control patches. We used data from an inventory of vegetation, droppings and browsing conducted in 2020. The results indicate that moose resides more often in the unburned areas two years after a forest fire. On the contrary, grouse utilized the burned patches more frequently than the surrounding forest. In the unburned patches, browsing pressure proved to be significantly higher for the total amount of browsed tree shoots of pine as well as rowan, aspen, willow and oak together. More top shoot damages were observed in the unburned patches. Our results show that grouse thrive on two-year-old fire fields, possibly because stressed pines are preferred. However, available fodder for moose is still scarce. Skogsbränder har under lång tid haft omfattande påverkan på våra landskap. I den boreala zonen är naturliga bränder speciellt viktiga ...